Carcass characteristics and tissue composition of commercial cuts of lambs fed with banana crop residues - Carmo, Tania Dayana do; Alves Franca, Xisto Antonio; Geraseev, Luciana Castro; Viegas, Carlos Renato [UNESP]; Costa Neto, Paulo Pedro; Duarte, Eduardo Robson; Bahiense, Raphael Nogueira (Univ Estadual Londrina, 2016)
The aim of this study was to evaluate the effect of substitution of Cynodon hay with banana plantation residue hay on the carcass characteristics and tissue composition of commercial cuts of feedlot Santa Ines lambs. Twenty-five whole lambs were used, with an average age of five months and an initial live weight of 26.95 kg (+/- 1.5), distributed in a completely randomized design with five treatments (1 = 40% Cynodon spp. hay + 60% concentrate; 2 = 20% banana leaf hay + 20% Cynodon spp. hay + 60% concentrate; 3 = 40% banana leaf hay + 60% concentrate; 4 = 20% banana pseudostem hay + 20% Cynodon spp. hay + 60% concentrate; 5 = 40% banana pseudostem hay + 60% concentrate) and five repetitions. The lambs were slaughtered on day 69 of the experiment. The variables evaluated were: live weight without fasting (LWWF), live weight post-fasting (LWPF), morphometric measurements in vivo and postmortem, hot and cold carcass weights (HCW, CCW), hot and cold carcass yield (HCY, CCY), biological performance and weight loss by chilling. The carcasses were divided into eight commercial cuts: neck, shoulder, foreshank and hindshank, breast and flank, loin, leg and rack. The leg, shoulder and loin were dissected into muscle, fat and bone. The animals fed on pseudostem hay showed higher LWWF, LWPF, body length, HCW and CCW; however, the HCY, CCY, morphometric measurements and commercial cut weights and yields were not altered by the treatments. The use of pseudostem hay allows for heavier carcasses; however, the use of coproducts changed the characteristics and carcass yield of the assessed commercial cuts.
Keywords: Musa spp.; pseudostem; coproducts